2011
DOI: 10.1002/asl.333
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale circulation anomalies associated with persistent low temperature over Southern China in January 2008

Abstract: A pre-existing anticyclonic anomaly over Scandinavia/western Russia played a crucial role in the persistent low temperature event over southern China in January 2008. This anticyclonic anomaly extended eastward along the arctic coast of the Eurasian continent, and then induced the persistent low temperature over southern China. Considering that anticyclonic anomalies over Scandinavia/western Russia rarely extended eastward to central Siberia, the simultaneous presence of this feature along with the vigorous Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 14 publications
4
37
0
Order By: Relevance
“…Time-mean anomalies of (a),(b) 500-hPa geopotential height (gpm; contour interval 5 30 gpm) and (c),(d) surface air temperature (colors) and areas with significant precipitation (green shading) for the two UB events averaged (left) from 30 December 2007 to 12 January 2008 (event 1) and (right) from 17 to 30 January 2008 (event 2). This leads to persistent low temperatures and snow-ice weather over southern China from 15 to 31 January 2008 (Wen et al 2009;Bueh et al 2011;Han et al 2011), but this is not the case for event 1 (Figs. In (c),(d), the dotted regions are above the 95% confidence level based on a two-sided Student's t test and the dark arrows denote the time-mean 850-hPa total wind vector.…”
Section: A Case Study Of the January 2008 Cold Event Overmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-mean anomalies of (a),(b) 500-hPa geopotential height (gpm; contour interval 5 30 gpm) and (c),(d) surface air temperature (colors) and areas with significant precipitation (green shading) for the two UB events averaged (left) from 30 December 2007 to 12 January 2008 (event 1) and (right) from 17 to 30 January 2008 (event 2). This leads to persistent low temperatures and snow-ice weather over southern China from 15 to 31 January 2008 (Wen et al 2009;Bueh et al 2011;Han et al 2011), but this is not the case for event 1 (Figs. In (c),(d), the dotted regions are above the 95% confidence level based on a two-sided Student's t test and the dark arrows denote the time-mean 850-hPa total wind vector.…”
Section: A Case Study Of the January 2008 Cold Event Overmentioning
confidence: 99%
“…The persistent cold temperatures and severe snow-ice weather over southern China in January 2008 are typical examples of extreme cold events over East Asia (Wen et al 2009;Han et al 2011;Bueh et al 2011). Thus, it is reasonable to classify the UB pattern in terms of its zonal and meridional positions.…”
Section: A Case Study Of the January 2008 Cold Event Overmentioning
confidence: 99%
“…This cyclone appears as a merge of the two wave trains. Previous studies have identified the effects on the cold events over East Asia of either the north wave train (Bueh et al, ; Hsu, ; Hsu & Wallace, ; Joung & Hitchman, ; Lau & Lau, ; Park et al, ; Song et al, ; Suda, ; Takaya & Nakamura, , , ; Wu & Chan, ; Yang & Li, ; Yao et al, ) or the south wave train (Song & Wu, ; Wen et al, ). Here, we detect that the two wave trains may coexist in association with intraseasonal variability of the East Asian winter monsoon.…”
Section: Two Wave Trains Associated With the East Asian Intraseasonalmentioning
confidence: 99%
“…The occurrence of East Asian cold events has been linked to a wave train over the middle-to-high latitude Eurasia (Bueh et al, 2011;Hsu, 1987;Hsu & Wallace, 1985;Joung & Hitchman, 1982;Lau & Lau, 1984;Park et al, 2011;Song et al, 2016;Song & Wu, 2017;Suda, 1957;Takaya & Nakamura, 2005a, 2005bWu & Chan, 1997;Yang & Li, 2016;Yao et al, 2016). The wave train propagates eastward along the polar jet stream.…”
Section: Introductionmentioning
confidence: 99%
“…For example, four consecutive years of cold winters occurred over Northern Asia from 2009/2010to 2012/2013(Bueh et al, 2011Buchan et al, 2014;Gong et al, 2014;Qiao et al, 2014). Under global warming, frequent cold winters over Northern Asia may have an impact on the subsequent spring and summer climate, but there has been little research focusing on this earlier signal.…”
Section: Introductionmentioning
confidence: 99%